In-situ Evaluation of Growth Rate and Yield Components of Several Non-tidal Swamp Rice Accessions in South Sumatera - Entis Sutisna Halimi; Rujito Agus Suwignyo; Mery Hasmeda; I. Rahmawati (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Halimi et al. 2012. In-situ Evaluation of Growth Rate and Yield Components of Several Non-tidal Swamp Rice Accessions in South Sumatera. JLSO 1(2):107-115Rapid increase of agricultural land conversion has led to the intensified utilization of non-tidal swamp. The objective of this research was to identify growth rate and yield components of several rice accessions of non-tidal lowland swamp of South Sumatera. This research incorporated the cultivation of nine rice accessions in non-tidal swamp area. Research plots were prepared by local farmers to include 27 plots of 280 cm x 80 cm following the Complete Randomized Block Design. Research indicated that rice accessions might be classified into 3 groups of Low Growth Rate (LGRA), Intermediate Growth Rate (IGRA), and High Growth Rate (HGRA) accessions. Each group has different growth rate according to the field water level during flooding season of < 5 cm, 5 to 6 cm, and >6 cm per week, respectively. The LGRA group consisted of Petek (A5) and Senia (A6), the IGRA group consisted of Bone (A1), Pelita Rampak (A2), and Sawo Rimbo (A7) and the HGRA group consisted of Kuning (A3), Siam (A4), Sawah Beling (A8) and Putih Olak (A9). Some yield components tended to decrease as the growth rate increased, and some varied depending on the accessions. For effective and efficient cultivation, farmers should apparently consider growth rate and yield potential to decide which rice accessions to grow.